Global Phylogenomic Analysis of Nonencapsulated Streptococcus pneumoniae Reveals a Deep-Branching Classic Lineage That Is Distinct from Multiple Sporadic Lineages. - Hilty, M; Wüthrich, D; Salter, S; Engel, H; Campbell, S; Sá-Leão, R; de Lencastre, H; Hermans, P; Sadowy, E; Turner, P; Chewapreecha, C; Diggle, M; et al. (2014)
The surrounding capsule of Streptococcus pneumoniae has been identified as a major virulence factor and is targeted by pneumococcal conjugate vaccines (PCV). However, nonencapsulated S. pneumoniae (non-Ec-Sp) have also been isolated globally, mainly in carriage studies. It is unknown if non-Ec-Sp evolve sporadically, if they have high antibiotic nonsusceptiblity rates and a unique, specific gene content. Here, whole-genome sequencing of 131 non-Ec-Sp isolates sourced from 17 different locations around the world was performed. Results revealed a deep-branching classic lineage that is distinct from multiple sporadic lineages. The sporadic lineages clustered with a previously sequenced, global collection of encapsulated S. pneumoniae (Ec-Sp) isolates while the classic lineage is comprised mainly of the frequently identified multilocus sequences types (STs) ST344 (n = 39) and ST448 (n = 40). All ST344 and nine ST448 isolates had high nonsusceptiblity rates to β-lactams and other antimicrobials. Analysis of the accessory genome reveals that the classic non-Ec-Sp contained an increased number of mobile elements, than Ec-Sp and sporadic non-Ec-Sp. Performing adherence assays to human epithelial cells for selected classic and sporadic non-Ec-Sp revealed that the presence of a integrative conjugative element (ICE) results in increased adherence to human epithelial cells (P = 0.005). In contrast, sporadic non-Ec-Sp lacking the ICE had greater growth in vitro possibly resulting in improved fitness. In conclusion, non-Ec-Sp isolates from the classic lineage have evolved separately. They have spread globally, are well adapted to nasopharyngeal carriage and are able to coexist with Ec-Sp. Due to continued use of PCV, non-Ec-Sp may become more prevalent.